2017
DOI: 10.1063/1.4978794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the matrix and intramolecular interactions on the stability of the higher-energy conformers of 2-fluorobenzoic acid

Abstract: DFT(B3LYP)/6-311++G(d,p) calculations on 2-fluorobenzoic acid (2FBA) show that the molecule has four conformers: two low energy conformers (forms I and II) with the carboxylic acid group assuming the cis configuration (O=C-O-H dihedral equal to 0°) and two higher-energy conformers (III, IV) with a trans carboxylic group configuration. Isolation of 2FBA monomers in argon or nitrogen matrices allows for the efficient trapping of both low-energy conformers. Narrowband selective near-IR(NIR) excitation of the 2νOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…The intramolecularly hydrogen bonded trans-II conformer of 2FBA is also a well-defined minimum with a high energy barrier (40.4 kJ•mol −1 ) of conversion into cis-II (see Figure 4, bottom-left panel), and has an expected population in the gas phase at room temperature of ca. 2% [16], justifying its experimental observation in the microwave experiment [18]. Trans-II was not detected in the deposited cryogenic matrices [16] most probably because its expected population in the matrix is below the sensitivity of the technique (the infrared spectra is complex, showing the vibrational signatures of the two cis conformers and the spectra of trans-II conformer is not much different from those of the cis forms, which complicates its experimental detection by this technique).…”
Section: Conformers and Barriers To Internal Rotationmentioning
confidence: 98%
See 4 more Smart Citations
“…The intramolecularly hydrogen bonded trans-II conformer of 2FBA is also a well-defined minimum with a high energy barrier (40.4 kJ•mol −1 ) of conversion into cis-II (see Figure 4, bottom-left panel), and has an expected population in the gas phase at room temperature of ca. 2% [16], justifying its experimental observation in the microwave experiment [18]. Trans-II was not detected in the deposited cryogenic matrices [16] most probably because its expected population in the matrix is below the sensitivity of the technique (the infrared spectra is complex, showing the vibrational signatures of the two cis conformers and the spectra of trans-II conformer is not much different from those of the cis forms, which complicates its experimental detection by this technique).…”
Section: Conformers and Barriers To Internal Rotationmentioning
confidence: 98%
“…2% [16], justifying its experimental observation in the microwave experiment [18]. Trans-II was not detected in the deposited cryogenic matrices [16] most probably because its expected population in the matrix is below the sensitivity of the technique (the infrared spectra is complex, showing the vibrational signatures of the two cis conformers and the spectra of trans-II conformer is not much different from those of the cis forms, which complicates its experimental detection by this technique). However, once trans-II is produced in situ by vibrational excitation (upon infrared irradiation) of the matrix-isolated conformer cis-II, the high energy barrier for the trans-II→cis-II conversion precludes this transformation to take place (the over the barrier thermal process is not possible at all, and the experiments showed that quantum mechanical tunneling is also inneficient in this case).…”
Section: Conformers and Barriers To Internal Rotationmentioning
confidence: 98%
See 3 more Smart Citations